Na co upozornilo politické zneuzívání psychiatrie ve vztahu psychiatrie a práva - Kalvach, Z (Ceskoslovenska psychiatrie, 1995)
The political abuse of psychiatry in the former USSR was enabled by: 1. a disproportionate pointing up of the medical criteria of mental disorder to the detriment of the social ones, above all by circumventing the sociological labelling process; 2. lack of control of involuntary psychiatric hospitalisation by the law; 3. an obsolete definition of psychiatry. The author suggests a definition of psychiatry taking into consideration both the above mentioned criteria and making the importance of the legal control of involuntary psychiatric hospitalisation more evident.
Keywords: Psychiatry; Commitment of Persons with Psychiatric Disorders; zodpovědnost duševně nemocného; lidé; dějiny 20. století; psychiatrie; Communism; History, 20th Century; komunismus; Humans; USSR; SSSR